2019
DOI: 10.1039/c8ta10250c
|View full text |Cite
|
Sign up to set email alerts
|

One-pot gamma ray-induced green synthesis of a Prussian blue-laden polyvinylpyrrolidone/reduced graphene oxide aerogel for the removal of hazardous pollutants

Abstract: Gamma-ray mediated synthesis of ultra-low dense porous 3D-network structured PB@PVP/rGO aerogel with high mechanical stability for the removal of Cs+ ions, methylene blue and n-hexadecane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…On the other hand, graphene aerogels are largely and almost exclusively proposed to remove a wide variety of pollutants from wastewater, including dyes [ 128 , 129 ], drugs [ 8 , 20 ], heavy metals [ 121 , 130 ], radioactive elements [ 28 , 29 ], bacteria [ 124 , 131 ], organic solvents [ 131 , 132 ], and oils [ 26 , 125 ]. GO-based aerogels have exhibited great potential for wastewater treatment and the purification of natural waters, such as removing mercury [ 133 ] and microcontaminants from drinking water [ 134 ].…”
Section: Graphene Oxide-based Aerogelsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, graphene aerogels are largely and almost exclusively proposed to remove a wide variety of pollutants from wastewater, including dyes [ 128 , 129 ], drugs [ 8 , 20 ], heavy metals [ 121 , 130 ], radioactive elements [ 28 , 29 ], bacteria [ 124 , 131 ], organic solvents [ 131 , 132 ], and oils [ 26 , 125 ]. GO-based aerogels have exhibited great potential for wastewater treatment and the purification of natural waters, such as removing mercury [ 133 ] and microcontaminants from drinking water [ 134 ].…”
Section: Graphene Oxide-based Aerogelsmentioning
confidence: 99%
“…In the last few years, GO-based aerogels have been proven to be excellent absorbent matrices for the removal of other heavy metal ions with genotoxic, mutagenic, and carcinogenic effects on humans and aquatic living organisms, including Pb(II) [ 121 , 134 ], Cu(II) [ 118 ], and Fe(III) ions [ 5 ]. In addition, the effective elimination of radioactive elements—known as radionuclides—was also proven in the studies of Huo et al [ 28 ] and Lee et al [ 29 ], specifically in the removal of Sr(II) and Cs + , employing polyvinyl alcohol (PVA)/GO and polyvinylpyrrolidone (PVP)/GO aerogels, respectively. It is common to involve polymers as crosslinkers and/or stabilizers in the production of GO-based composites.…”
Section: Graphene Oxide-based Aerogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, ionizing radiation constitutes a potential powerful method for advanced nanomaterial preparation. As a highly penetrative electromagnetic wave with the highest photon energy, gamma radiation has been attempted in the wet-chemical preparation of metal [19][20][21] , oxide [22][23][24][25] and carbonbased materials [26][27][28] . When the solution concentration is low, solvent is the dominating species that interacts with gamma rays.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the preparation of porous polymer aerogels by a freeze-drying method has been investigated. [24][25][26][27][28] This method exhibits great advantages of simplicity and controllability, which has been widely studied and applied in various fields. [29][30][31][32][33] It has been reported that a GO-PVA aerogel was successfully obtained, 34 as PVA can be used as the skeleton to support GO.…”
Section: Introductionmentioning
confidence: 99%